Application of vancomycin in patients with augmented renal clearance. Issue 5 (9th January 2019) - Chu, Yang; Luo, Yifan; Jiang, Mingyan; Zhou, Baosen
Abstract : Objective: To analyse the influence of factors on the steady-state trough concentration (Ctrough ) of vancomycin, especially in patients with augmented renal clearance, and to provide a reference for clinical application. Methods: Data on patient demographics, routine blood examination, hepatic function and kidney function were collected from May 2013 to October 2016. A total of 292 patients were enrolled and correlations between Ctrough of vancomycin and other test indices were analysed by SPSS software. Results: The patients with augmented renal clearance were significantly younger with relatively lower Ctrough values and higher weight, ALB and PLT compared to others. And age was the most important factor of Ctrough among subgroups of ARC. Conclusions: Inpatients with augmented renal clearance, vancomycin Ctrough was mainly affected by age. Clinicians and pharmacists should adjust the dosage regimen in a timely manner based on therapeutic drug monitoring and these influencing factors.